MENINGKATKAN KEMAMPUAN MENCOCOK GAMBAR MELALUI METODE DEMONSTRASI PADA KELOMPOK B DI ROUDHOTUL ATFHAL AL FATAH TARIK SIDOARJO - ANDRIANINGSIH, SRIANA (Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2017)
?Abstrak: The method used in improving the ability to match is by demonstration method. The benefits of matching are to train hand coordination, eye and concentration, increase confidence, smooth writing, expressions and cognitive honing. This research used classroom action research with teacher as researcher, using spiral system of early reflection as much as two cycle, each cycle consist of preparation of research plan, execution, observation and reflection. The data collection method used observation, where the purpose of successful research is said to succeed when the observation sheet ability to match the image in children reaches ? 80%. The target of this research is the children of group B Roudhotul Atfhal Al Fatah Tarik Sidoarjo which amounted to 22 children. This research was conducted for 2 months in Roudhotul Atfhal Al Fatah Tarik Sidoarjo.?Kata Kunci: Kemampuan mencocok Gambar, Metode Demonstrasi